INTEGRASI AL-QURAN DAN HADITS DALAM PEMBELAJARAN AKHLAK ANAK USIA DINI: PERSPEKTIF LITERATUR - Fhusilat, Fhusilat (Cahaya Ilmu Bangsa Institute, 2025)
Education of morals in early childhood is a crucial foundation in the formation of the character of the next generation. The Qur'an and Hadith, as the main sources of Islamic teachings, have a central role in guiding humans towards noble morals. This study aims to examine how the integration of the values of the Qur'an and Hadith can be carried out in early childhood moral learning through a literature perspective. This literature study approach was chosen because it allows researchers to analyze various sources of information and experiences from experts and education practitioners. Data were collected from scientific journals, books, and other related documents, then analyzed qualitatively to identify relevant themes, methods, strategies, and effective approaches in the integration of these values. The results of the study are expected to provide valuable insights for educators, parents, and other stakeholders in designing and implementing effective moral learning for early childhood.